Relationship between Reaction Time and Deception Type during Smash in Badminton - El-Gizawy, Helal; Akl, Abdel-Rahman (Journal of Sports Research, 2015)
The purpose of the present study was to determine the relationship between reaction time and deception type and investigate the effect of deception type on reaction time during smash in Badminton. Sex Badminton players are high level athletes in the world participated in the last Olympic championship "London 2012", (mass 69.17±6.31 kg, length 178.00±0.06 cm. Reaction time is defined as the period of time that elapses between offensive player stroke the shuttle and opponent player move to shuttle direction. Smashes were analyzed of the last six matches in Olympic championship London 2012, two matches in Quarter-finals, two matches of Semi-finals, Bronze Medal Match and Gold Medal Match. Dartfish v.7 software motion analysis used to analysis 230 smashes and for the statistical analysis of the data the IBM SPSS Statistics 21 was used. The complex deception is more difficult types of deception for the opponents as the player use more than a tool during the striking and then the degree of difficulty followed by arm deception, while the performance of the smashes without deception gives a greater opportunity for an opponent to anticipate the strike and then stopped, and this means that the increase the degree of difficulty of deception increased the time of reaction necessary to repel the strike, thereby increasing the opportunity to make the point, therefore must specify a part in the content of the training programs for the smashes combined with different types of deception.